Transcending the borders of countries, languages, and disciplines in Russian émigré culture - Flamm, Christoph; Marti, Roland; Raev, Ada (Cambridge Scholars Publishing, 2018)
The political changes at the end of the last century in the Soviet Union, and later the Russian Federation, had deep-reaching repercussions on the interpretation of Russian culture in the time of division between ""Russia Abroad"" and ""Russia at Home"". Ever since, scholars have tried to understand and to describe the interrelationship between the two Russias. In spite of intensive research, numerous conferences and publications, there are still many discoveries to be made and a number of questions to be answered. This volume presents a selection of articles based on papers presented at an int